Corporate Liability of Pharmaceutical Companies Producing Unsafe Drugs (Lesson-Learnt from the USA) - Hanifah Febriani; Bagus Mulia Pandu Winoto; Carissa Maharani (Lembaga Penelitian dan Pengabdian Masyarakat, 2023)
Since the end of 2022, Indonesia has been concerned with cases of kidney failure in children. Long before that, United States of America (USA) have experienced in handling the case of pharmaceutical company. This research aims to examine the Corporate Liability Settlement for the Pharmaceutical Industry Producing Unsafe Drugs in United States and Indonesia as well as to elaborate more about what Indonesia can improve reflecting from the cases in America. This is normative legal research, using comparative methodology as an approach. The research has found that Indonesia shall address the idea to settle the case with plea agreement, civil lawsuit, as well as oblige the corporation to enter in corporate integrity agreement. Furthermore, a higher amount of fine is required in order to deter the company.